Poverty, the Bible, and Africa: Contextual Foundations for Helping the Poor - Boaheng, Isaac (HippoBooks, 2020)
Poverty reduction is a worldwide concern, yet if the church is to play an effective role in its alleviation, an approach that is both biblical and contextual is required. In Poverty, the Bible, and Africa, Isaac Boaheng formulates a theology of poverty that engages Scripture, African traditional wisdom, and contemporary African concerns to create a paradigm for understanding and alleviating poverty in Africa. Boaheng highlights that, whatever our cultural context, God frowns upon materialism, extravagance, and love for riches; yet the author also demonstrates why a contextual theology must address people's societal and cultural needs alongside spiritual ones. If we desire a model for poverty reduction that is both theologically sound and contextually appropriate, we must facilitate an encounter between the teachings of Scripture and the socioeconomic , political, and religious realities of a particular context. Combining in-depth cultural analysis with careful exegetical reflection, this book offers refreshing insight into the challenge of confronting poverty in Africa. Boaheng's approach, however, is relevant far beyond the continent and is transferable to any context where others are seeking to effectively understand and combat poverty. This is an important book on the subject of poverty in Africa. The author approaches it from a theological perspective and offers a constructive critique aimed at correcting misplaced notions of wealth and poverty in the African context. It is highly recommended for the academy, church readership, and national policy makers. Boaheng brings solid exegesis as he reframes the challenges of poverty and injustice. He does not hold back on challenging aberrant theology, colonial injustice, and issues such as corruption, which create barriers for people to experience "fullness of life. " At the same time Boaheng helps unpack how the rich cultural heritage across African societies can be a strong foundation to build upon, rather than importing solutions which are culturally and contextually inappropriate from the global north. This should be on the required reading list for everyone involved with mission and development in Africa.
Keywords: Religion / Christian Living / Social Issues; Religion / Christian Theology / General; Social Science / Poverty & Homelessness